Physical Effects On The Interactions Of CO2 Laser On The Teeth - Ahmad, Alwani Liyana (2010)
Recent studies have shown that CO2 lasers can successfully be used at low-power densities to fuse enamel, dentin, and apatite. In this study, forty nine samples of different types of extracted human teeth were irradiated under low power continuous wave CO2 laser. The mass, density, and thickness of each type of teeth were recorded before and after irradiation. Density and thickness of the sample was measured using gas pycnometer and gamma spectroscopy with Americium-241 source, respectively. Chemical compounds of teeth were determined using Fourier Transform Infrared Spectroscopy (FTIR), diameter of penetration with biological microscope, and the penetration depth was calculated by differentiation of thickness before and after irradiation.